Anatomical study on the stifle (knee) joint in local breed of Awassi sheep - Adnan A. Alhasso; Ammar Gh. Al-Haaik; Mowaffak J. Yousif (Iraqi Journal of Veterinary Sciences, 2023)
This study focuses on the knee joint of Awassi sheep in Nineveh Governorate to identify its morphological characteristics. Ten healthy knee joints were used from both sexes. Our study showed that the knee joint is a complex joint consisting of a femur-patellar and a femur-tibial articular surfaces. The femoral-patellar articular surface is formed among the ridges of the femoral trochlea, which comprises two parallel and oblique ridges, as the medial ridge continues with medial condyloid of femur and lateral ridge separates from lateral condyle by the extensor fossa. The patella bone is the other part of this articulating surface, smaller than the trochlear articular surface. The articular capsule is thin and wide, and it is a fibrous layer that connects and lies around articular surfaces' edges, which are strengthened medially and laterally by femoral-patellar ligaments, both medial and lateral. The femoral-patellar joint contains the medial and lateral femoro-patellar ligaments, which are in the form of straps that connect the patella bone to the tibia and the middle patellar ligament. The two femur condyles and the proximal end of the tibia come together to form the tibial-femoral articular surface, with meniscus cartilage overlapping. The medial and lateral menisci are crescent-shaped sheets of fibrocartilage corresponding to the femoral and tibial articular surface. Each meniscus is connected to the tibia anteriorly by the anterior tibial meniscus ligaments, the medial meniscus attached posteriorly to the tibia by posterior cartilaginous ligament, and the lateral meniscus cartilage posteriorly bonded to the femur by the cartilaginous meniscofemoral ligament. The fibrous sheet of the articular capsule is connected around the edges of the condyles of femur and tibia, and articular capsule is attached to the medial and lateral tibiofemoral ligaments. There are two vesicular sacs with a simple connection between the cruciate ligaments. This study concluded that the fibrous sheet of the articular capsule is connected around the edge’s condyles of femur and tibia, and the articular capsule is attached to the medial and lateral tibiofemoral ligaments. There are two vesicular sacs with a simple connection between the cruciate ligaments.